2022
DOI: 10.3389/fgene.2022.867909
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteome Profiling of Saliva Between Estrus and Non-Estrus Stages by Employing Label-Free Quantitation (LFQ) and Tandem Mass Tag (TMT)-LC-MS/MS Analysis: An Approach for Estrus Biomarker Identification in Bubalus bubalis

Abstract: Accurate determination of estrus is essentially required for efficient reproduction management of farm animals. Buffalo is a shy breeder and does not manifest overt signs of estrus that make estrus detection difficult resulting in a poor conception rate. Therefore, identifying estrus biomarkers in easily accessible biofluid such as saliva is of utmost interest. In the current study, we generated saliva proteome profiles during proestrus (PE), estrus (E), metestrus (ME), and diestrus (DE) stages of the buffalo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…The inhibited activities of C3 and TF may have effects on immunosuppressive that protect the epididymal sperm against autoimmune responses and the establishment of immune tolerance [ 51 , 52 ]. SERPINB1 has multiple modulatory roles in regulating the immune response and cellular homeostasis and the decreased abundance of SERPINB1 may be linked to the enhanced sex steroid hormone stimulus with the advancement of development [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibited activities of C3 and TF may have effects on immunosuppressive that protect the epididymal sperm against autoimmune responses and the establishment of immune tolerance [ 51 , 52 ]. SERPINB1 has multiple modulatory roles in regulating the immune response and cellular homeostasis and the decreased abundance of SERPINB1 may be linked to the enhanced sex steroid hormone stimulus with the advancement of development [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on differential expression of mRNA transcripts [44][45][46], heat shock proteins [47][48][49][50] and other proteins [44,[51][52][53][54] in various biological fluids and/or tissues collected at different stages of estrous cycle have been reported and the use of the same as biomarkers for the identification of estrus has been opined.…”
Section: Differential Expression Of Mrna and Proteins During Various ...mentioning
confidence: 99%
“…Therefore, specific biomarker needs to be identified for accurate detection of estrus in buffaloes. Previous studies have shown the use of salivary RNA (Joshi et al., 2023; Onteru et al., 2016), protein biomarkers (Singh et al., 2022), urinary pheromones or faecal volatile compounds as reliable indicators of estrus in buffalo (Karthikeyan et al., 2013; Muthukumar et al., 2018). Along with that, a salivary ferning pattern has also been recommended for detecting estrus even in the absence of cervicovaginal fluid (CVF) discharge in buffaloes (Ravinder et al., 2016; Surla et al., 2021).…”
Section: Introductionmentioning
confidence: 99%